Chapter 31: AI algorithmic oversight: new frontiers in regulation - Busuioc, Madalina (Edward Elgar Publishing, 2022)
The rise of artificial intelligence is transforming our societies, permeating an ever-expanding array of domains ranging from finance to employment or healthcare. Public regulators, too, increasingly rely on machine learning techniques in the discharge of regulatory tasks - for instance, in prioritising regulatory targets for regulatory attention and/or enforcement, in areas as varied as environmental protection, securities or food safety. But the use of AI in government stretches well beyond the field of regulation, making significant inroads into the coercive and (re)distributive powers of the state itself. The current chapter highlights important challenges arising for regulation in this area, brought on by the specificities of artificial intelligence technologies, and the often high-stakes nature of their deployment in both public and private contexts. It explores the potential advantages and disadvantages of different modes of intervention in governing the development and deployment of artificial intelligence systems. Simultaneously, it flags critical aspects for consideration by regulators in this respect, speaking also to recent draft regulatory efforts in the EU.